2020
DOI: 10.1177/1534735420906463
|View full text |Cite|
|
Sign up to set email alerts
|

Xiao-Ai-Ping Injection Enhances Effect of Paclitaxel to Suppress Breast Cancer Proliferation and Metastasis via Activating Transcription Factor 3

Abstract: Chemotherapy is an effective treatment for invasive breast cancer. Paradoxically, many recently published findings showed that the first-line chemotherapeutic agent paclitaxel (PTX) showed pro-metastatic effects in the progress of treating breast cancer. Xiao-Ai-Ping (XAP) injection, composed of a traditional herbal medicine, Marsdenia tenacissimae extract, is known to exert antitumor effects on various cancers. However, there are few experimental studies on breast cancer. The underlying mechanism of the antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In vivo , experiments also confirmed that the combination enhanced the inhibitory effect on tumor cells. These results suggest that XAP enhances PTX efficacy by inhibiting ATF3 ( 148 ). TNBC is a special subtype of breast cancer and is a refractory tumor.…”
Section: Chinese Patent Medicinementioning
confidence: 71%
“…In vivo , experiments also confirmed that the combination enhanced the inhibitory effect on tumor cells. These results suggest that XAP enhances PTX efficacy by inhibiting ATF3 ( 148 ). TNBC is a special subtype of breast cancer and is a refractory tumor.…”
Section: Chinese Patent Medicinementioning
confidence: 71%
“…Firstly, Xiao-ai-ping alone (particularly via injection route) exhibits direct anticancer effect in different cancer cell lines and animal tumor xenografts 47 , 48 . Secondly, the injectable Xiao-ai-ping enhances the antitumor effects of several anticancer drugs through various mechanisms including the inhibition of CYP3A4 activity, downregulation of activating transcription factor 3 (ATF3), and suppression of pregnane X receptor (PXR) expression and downstream targets 49 , 50 , 51 . Moreover, our research team also reported that several POPs in M. tenacissima inhibited the MDR ABC transporters and potentiated the cytotoxic effect of chemotherapeutic drugs previously 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, some BRCA treatments, like mastectomy, chemotherapy, and radiotherapy, have serious side effects ( Miller et al, 2016 ). Chemotherapy is more effective than mastectomy and radiotherapy for metastatic cancer ( Chen et al, 2020 ); however, conventional chemotherapeutic drugs are associated with serious side effects such as neutropenia, stomatitis, and mucositis ( Hesketh Paul et al, 2004 ). Nanoparticle-based cancer vaccines are currently being developed and are in the early stages ( Wen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%